Johanssonian Investigations Essays in Honour of Ingvar Johansson on His Seventieth Birthday - Svennerlind, Christer; Almäng, Jan; Ingthorsson, Rögnvaldur (EIDE, 2013)
In the last decades, Ingvar Johansson has made a formidable contribution to the development of philosophy and particularly that of metaphysics. This volume consists of original papers written by 50 philosophers from all over the world to celebrate his 70th birthday. The papers cover traditional issues in metaphysics and the philosophy of mind, applied ethics, applied metaphysics, the nature of human rights, the philosophy of economics and sports.